Forensic engineering for machine foundations. (1st January 2013) - Lakshmanan, N.; Muthumani, K.; Gopalakrishnan, N.
Machine foundations are dynamically loaded structures whose response depends on a number of parameters such as strength, stiffness, mass, damping, soil–structure interaction and fatigue. Performance-based designs and evaluation procedures are gaining popularity particularly with respect to structures that have been built using codal provisions existing a few decades back. Enhancement of knowledge has led to various changes. But, machine foundations that have been designed and constructed in the past are seldom checked for their suitability using the present day knowledge. Some parameters that have been omitted or inadequately considered lead to malfunctioning of machine foundations. A four stage forensic engineering procedure is proposed for rehabilitation of these foundations. The stages involved are discussed taking three case study examples handled by the authors. It is felt extremely important that such investigations are documented and discussed by experts is engineering profession so that they can be used widely by practicing engineers.